Thromboelastography Does Not Detect Preinjury Antiplatelet Therapy in Acute Trauma Patients. Issue 2 (February 2016) - Daley, Mitchell J.; Trust, Marc D.; Peterson, Evan J.; Luftman, Kevin; Miller, Andrew H.; Ali, Sadia; Clark, Adam; Aydelotte, Jayson D.; Coopwood, Thomas B.; Brown, Carlos V.R.
Thromboelastography (TEG) with platelet mapping has been proposed as an assay to detect the presence of antiplatelet agents (APA), yet no study has evaluated TEG markers of platelet dysfunction in acute trauma patients stratified by the use of preinjury APA. We hypothesized that patients on preinjury APA would demonstrate prolonged TEG markers of platelet dysfunction compared with those not on preinjury APA. This retrospective review evaluated all trauma patients admitted to a Level I trauma center from February 2011 to April 2013 who received a TEG within the first 24 hours of admission. Patients were classified as receiving preinjury APA or no APA if their documented medications included either aspirin or adenosine diphosphate (ADP) antagonists, including clopidogrel, prasugrel, and ticagrelor. A total of 129 patients were included (APA, n = 35; no APA n = 94) in the study. The time from admission to the first TEG was similar (APA 175 ± 289 minutes versus no APA 216 ± 321 minutes, P = 0.5). There was no significant difference in TEG markers of platelet dysfunction, including per cent ADP inhibition (APA 61.7 ± 25.8% versus no APA 62.3 ± 28.8%; P = 0.91) or per cent arachidonic acid inhibition (APA 58.2 ± 31% versus no APA 53.8 ± 34%; P = 0.54). Both groups had similar proportion of severe platelet dysfunction, defined as ADP inhibition greater than 70 per cent (APA 40% versus no APA 40%; P = 0.8) and arachidonic acid inhibition greater than 70 per cent (APA 40% versus no APA 39%; P = 0.89). In conclusion, platelet dysfunction after major trauma is common. Therefore, TEG alone should not be used to evaluate for the presence of APA due to apparent lack of specificity.